113 AUDIT: DELIRIUM RECOGNITION ON AN ACUTE MEDICAL WARD. (25th October 2022) - Gibbons, C; Harte, O; O'Donnell, G; Kelleher, R; Mulpeter, K
Abstract: Background: One-third of older general medical patients have delirium; it is present in half of these patients on admission and develops during hospitalisation in the other half. Despite its high prevalence, delirium is frequently not recognised, evaluated or managed appropriately resulting in poor outcomes. Our aim was to assess whether or not delirium was being recognised and documented on the General Medical Wards (GMW). Methods: We completed a prospective chart review using an audit tool on all patients aged ≥65 years on a GMW and a Specialist Geriatric Ward (SGW) over a 24-hour period. We screened all identified patients using the 4AT Test. The standard measured against was the HSE Guideline – Delirium on General Hospital Wards: Identifying Patients at Risk, Delirium Screening and Next Steps. Results: We included 27 patients in the study (n=27) – median age was 80 years (range 65-90); 17 were male (62.96%); 10 were on a SGW (37.04%). There was a 4AT documented on 9 (n=10) of the patients on the SGW (90%) in comparison to 0 (n=17) on the GMW (0%). We identified n=7 patients with a 4AT ≥4 consistent with acute delirium – 4 were on the SGW (57.14%). All 4 of these patients (n=4) were documented as delirious on the SGW (100%). Of the 3 patients identified on the GMW (n=3), 1 was documented as delirious (33.33%). All patients with delirium (n=7) had non-pharmacological measures implemented (100%), most commonly catheter avoidance (100%), analgesia (100%) and regular mobilization (85.71%). Pharmacological management was administered in 2 cases (28.57%). Conclusion: Our audit demonstrates that despite a high prevalence of delirium amongst older adults on GMWs, it remains under-recognized missing a pertinent opportunity to investigate and initiate management. This may result in adverse outcomes. The first step in improving care in older adults suffering from delirium is detection. Detection begins with screening.